2011
DOI: 10.3892/ijo.2011.1031
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of high-risk HPV in benign and malignant lesions of the larynx

Abstract: Abstract. The aim of this study was to determine the prevalence of human papillomavirus (HPV) in patients with laryngeal benign lesions (LBLs) and laryngeal squamous cell carcinomas (LSCCs) using a sensitive E6/E7 type-specific PCR. Paraffinembedded samples from LBL (n=39) and LSCC patients (n=67) were evaluated for the presence of HPV DNA by GP5 + /GP6 + consensus PCR and E6/E7 type-specific PCR for HPV types 6,11,16,18,31,33,35, 39, 45, 51, 52, 53, 56, 58, 59, 66 and 68. In LSCCs, immunohistochemical stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…High-risk-HPV DNA has been found in benign and normal tissue of the larynx (Garcia-Milian et al , 1998; Duray et al , 2011), supporting the idea that HPV DNA presence alone cannot demonstrate causality. The concept for causal involvement of mucosal HPV in the pathogenesis of SCC includes: (a) presence of at least one viral genome copy per tumour cell, (b) active transcription of the viral oncogenes E6 and E7 and (c) interaction of the viral oncoproteins with central cellular regulator proteins of cell cycle and apoptosis signalling (Dyson et al , 1989; Scheffner et al , 1990; zur Hausen, 2006).…”
mentioning
confidence: 78%
“…High-risk-HPV DNA has been found in benign and normal tissue of the larynx (Garcia-Milian et al , 1998; Duray et al , 2011), supporting the idea that HPV DNA presence alone cannot demonstrate causality. The concept for causal involvement of mucosal HPV in the pathogenesis of SCC includes: (a) presence of at least one viral genome copy per tumour cell, (b) active transcription of the viral oncogenes E6 and E7 and (c) interaction of the viral oncoproteins with central cellular regulator proteins of cell cycle and apoptosis signalling (Dyson et al , 1989; Scheffner et al , 1990; zur Hausen, 2006).…”
mentioning
confidence: 78%
“…Numerous methodologies exist for direct testing for HPV, however, in situ hybridization is the most universally used method allowing for screening of all known high risk HPV types (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, and 66) in one test on standard paraffin tissue sections 66, 67 . Limited availability of this methodology for testing in the community, and concern for lower sensitivity compared to polymerase chain reaction (PCR) led to the evaluation of p16 as a surrogate marker for the presence of HPV in tumor cells.…”
Section: Prognostic Biomarkers For Hnsccmentioning
confidence: 99%
“…HPV detection and typing of paraffin-embedded tissues were performed as described in our previous work [9]. DNA extraction was performed using a QIAamp DNA Mini Kit (Qiagen, Benelux, Belgium), according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we demonstrated that HPV+ oral SCC patients with a history of tobacco use and/or alcohol consumption have a significantly poorer prognosis compared to HPV− patients [4], and two Swedish studies reported that oral HPV infection is associated with a dramatically increased risk of recurrence in oral SCCs [5, 6]. However, other studies have failed to demonstrate an association between HPV status and prognosis [79]. Therefore, it seems clear that the biology of oropharyngeal tumors in younger patients, nondrinkers, and nonsmokers is distinct from that of nonoropharyngeal SCC in older patients and those with a history of tobacco use and/or alcohol consumption [10].…”
Section: Introductionmentioning
confidence: 99%